A polyethylene terephthalate (PET) depolymerization recycling plant in the Philippines a plant design - Gonzales, David T.; Molina, Edward Jozef G.; Sanchez, Leandro Angelo Miguel L.
The design project is about designing a polyethylene terephthalate or PET plastic recycling plant via depolymerization and repolymerization of PET wastes in the Philippines.Preliminary studies in the feasibility study, A Polyethylene Terephthalate (PET) Depolymerization Recycling Plant in the Philippines, showed that a PET recycling plant is feasible in the Philippines given the volume of post PET waste generated and the demand for PET pellets. Major changes in this study from the feasibility study include the removal of supercritical carbon dioxide as a solvent, a decrease of a daily basis from 50 tons to 33 tons of PET waste and the division of the main stream into 2 streams from the dryers onwards.The daily basis of the recycling plant was changed to a lower value to get a more realistic percent of the market. Instead of obtaining around 93% of the PET wastes produced, 61% is taken. Also, the capacity of 50 tons per day is usually in excess of the capacities of current polymer recycling equipment. This is also one of the reasons why the main streams is divided into 2. The main stream is divided into 2 streams from the dryer onwards since larger equipment for this type of processing is not readily available. Fabricating new types of equipment will prove costly and economically disadvantageous. Also, dividing the streams into 2 can also be useful when processing 2 different types of PET sources. Since the process can also be easily done in batches, different qualities of PET can be separated to maintain and control the quality of the final products. PET plastic is a non-biodegradable polymer plastic mainly used for bottling and containers. There are no major producers of PET plastic in the Philippines since these PET products are mostly imported from countries such as Korea, Japan, Indonesia, Taiwan and USA (Basila & Valencia, 2000). An average of 24,000 tons is imported into the Philippines each year. The PET plastic brought into the country in the form of pellets, finished bottles and other products. Because these PET products are mostly used for consumer product, it will eventually be converted to wastes. An estimated 0.14 percent of the total solid waste of the Philippines is composed of PET plastics. By 2010, it is predicted that around 14.06 million tons of solid waste will be produced annually. From these, 19,500 tons of PET waste is produced. Although PET plastic is easily recyclable, it is only processed into lower grade plastic not applicable for the bottling industry. Most collected PET wastes are either melted into other uses such as non-food containers or are cleaned and shipped out to other countries which have the technology to further recycle the plastics.The waste collection is mentioned to be only 40 percent efficient and only 13 percent of the solid wastes are being recycled as of 2000 in the Philippines. Fortunately, the amount of solid wastes are being recycled show an increasing trend as compared with the 6 percent recycling in 1997 (The World Bank, 2001). Further improvements in the collection and segregation of solids wastes are expected in the future as the Republic Act (RA) 9003 is currently being implemented. Recycling in the Philippines is expected to play a major role in the development of the country as revenues from this industry show an increasing trend. The plant location is proposed to be in Valenzuela where a large number of plastic recycling plants are located. This would help provide easier sourcing and delivery of PET wastes since a transportation system is already present.Because the recycling of wastes is a main concern of communities, corporations and the government, programs for more efficient waste collection and segregation can be arranged to ensure a constant raw material supply for the recycling plant. This can also provide for cheaper PET wastes as feed. Recycling of wastes can also be sold as a service and thus can be endorsed by the Department of Environment and Natural Resources (DENR) in their programs regarding RA 9003. The current study is concluded to be feasible. However, a stable market value for the PET wastes should be considered and prepared beforehand.The proposed plant will have a fixed capital investment of PHP 420,600,000.00. With a rate of return equal to 28 percent and net profit of PHP 119,830,880.00.